Feminist Activism against Rape Culture. Issue 1 (1st March 2021) - Mitchell, Claudia
Abstract : I met Roxanne Harde, the guest editor of this Special Issue, at the Second International Girls Studies Association conference in 2019 when I attended the panel discussion, "Representations of Rape in Young Adult Fiction." I recall Roxanne's passion vividly and, indeed, the enthusiasm of all three presenters as they discussed a variety of texts in superb presentations that aligned well with Ann Smith's notion of feminism in action in their seeing "a fictional text not only as a literary investigation into issues of concern to its author but also as the site of educational research" (2000: 245). Their papers pointed to the ways in which the analysis of how rape culture is treated in Young Adult (YA) literature, film, and the print media can take scholars and activists so much further into the issues, and, at the same time, noted the ways in which rape culture in all its manifestations as a global phenomenon has inevitably led to its becoming an everyday topic of YA fiction.